2020
DOI: 10.3390/cells9040989
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Acidosis Promotes Metastatic Potency via Decrease of the BMAL1 Circadian Clock Gene in Breast Cancer

Abstract: Circadian oscillation is an essential process that influences many physiological and biological mechanisms and a decrease of circadian genes is associated with many diseases such as cancer. Despite many efforts to identify the detailed mechanism for decreasing circadian genes and recovering reduced circadian genes in cancer, it is still largely unknown. We found that BMAL1 was reduced in tumor hypoxia-induced acidosis, and recovered by selectively targeting acidic pH in breast cancer cell lines. Surprisingly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 58 publications
0
11
0
2
Order By: Relevance
“…Additionally, altered circadian rhythms have been reported to be correlated with the prognosis of breast cancer [61].The exist circadian rhythm and the core circadian gene Bmal1, persist in malignancy breast cancer cells [61]. Tumor hypoxia-induced acidosis decreases the transcription activation and protein stability of BMAL1 to promote breast cancer metastasis in vitro [62]. Moreover, members of PER subfamily, including PER-1, PER-2, and PER-3, have been reported to be lowly expressed and play significant role in NSCLC patients [63].…”
Section: Disruption Of the Circadian Clock Contributes To Cancermentioning
confidence: 99%
“…Additionally, altered circadian rhythms have been reported to be correlated with the prognosis of breast cancer [61].The exist circadian rhythm and the core circadian gene Bmal1, persist in malignancy breast cancer cells [61]. Tumor hypoxia-induced acidosis decreases the transcription activation and protein stability of BMAL1 to promote breast cancer metastasis in vitro [62]. Moreover, members of PER subfamily, including PER-1, PER-2, and PER-3, have been reported to be lowly expressed and play significant role in NSCLC patients [63].…”
Section: Disruption Of the Circadian Clock Contributes To Cancermentioning
confidence: 99%
“…Membranes were blocked in 5% skim-milk for 1 h and incubated with primary antibodies overnight at 4 °C. Membranes were incubated with a horseradish peroxidase (HRP)-conjugated secondary antibodies for 1 h, and then visually evaluated by using the ECL detection kit (Biomax Co., Ltd, Seoul, Korea) 27 .…”
Section: Characterizationmentioning
confidence: 99%
“…In addition, abnormal expression levels of circadian clock genes are closely related to tumor development. Studies have found that mutations in BMAL1, CRY1, and CRY2 are often associated with a higher risk and recurrence of acute myeloid leukemia and endometrial, ovarian, colorectal, and breast cancers ( Hasakova et al, 2018 ; Burgermeister et al, 2019 ; Kwon et al, 2020 ). Per 1 , Per 2 , and Per 3 are frequently expressed in human breast and colorectal cancers, non-small-cell lung cancer (NSCLC), hepatocellular and cervical squamous cell carcinomas, and glioma ( Yeh et al, 2005 ; Mostafaie et al, 2009 ; Lin et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%